Pyoderma gangrenosum: proposed pathogenesis and current use of biologics with an emphasis on complement C5a inhibitor IFX-1. (1st November 2020) - Lu, Justin D.; Milakovic, Milica; Ortega-Loayza, Alex G.; Marzano, Angelo V.; Alavi, Afsaneh
ABSTRACT: Introduction: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis with no FDA-approved treatment. The complement pathway has received renewed attention because it is elevated in inflammatory cutaneous conditions such as hidradenitis suppurativa (HS) and psoriasis. IFX-1 is a complement C5a inhibitor which inhibits neutrophil activation, chemotaxis, and reduces inflammatory signaling and complement driven tissue damage in various diseases. Areas covered: The article discusses a proposed pathogenesis of PG, early clinical investigations of IFX-1 for the treatment of HS and PG, its potential as a treatment for PG, and those other biologics currently under investigation. Expert opinion: Further studies should explore how patients with PG and other neutrophilic conditions may respond to complement inhibitors such as IFX-1. C5a blockade led to a reduction in inflammatory tunnels in HS, and alteration in neutrophil migration and activation supports the role of this pathway in the development of PG. The main challenges to the approval of IFX-1 are the identification of the optimal dose, duration, and stage-dependent factors in cutaneous inflammatory disorders. Further studies are required; however, complement inhibitors such as IFX-1 could find a place in clinical practice in years to come for severe, resistant PG that does not respond to conventional therapies.